Perspectives from historical analyses of agri-food system transformations: A case study of Odisha, India - Sarkar, Anindita; Mukherji, Aditi (Elsevier, 2025)
Rural society in Odisha, India, has been associated with widespread poverty and low purchasing power since the British colonial times. Odisha has consistently reported lower yields of crops and input use in agriculture compared to the national Indian average since India’s independence in 1947. Poor agricultural growth and rural poverty could be traced to colonial, extractive land revenue administration and poor land management practices. Post-independence scholarship has ascribed the continuation of rural poverty and distress to high exposure to natural hazards and high societal vulnerability due to development deficits. By analysing the historical evolution of policies since the 1850s, the study finds that even though the political and economic contexts have changed, low investment in agriculture remains the primary challenge even today. The cycle of low capital investment in agriculture, lack of adoption of better farm technologies, and overall public sector neglect of the agriculture sector has perpetuated, leading to low productivity. Therefore, it is time for the present policies to break away from these historical path dependencies to create a just and sustainable future for Odisha’s agri-food system.